Gram-scale production of forskolin in yeast through biosynthetic network elucidation and pathway optimization - Meiling Jiang; Hao Tang; Ying Ma; Zhenjiang Tian; Wenbo Xu; Xinqi Song; Lan Kang; Luqi Huang; Yating Hu (Bioresource Technology, 2026)

Chemical reaction driven interfacial reconstruction of In2O3/S-BiOCl heterojunction with Ag2S quantum dots enables a self-validated fluorescence/photoelectrochemical dual mode nitrite sensing - Jingshu Li; Yuee Zhong; Manqi Li; Jiawei Zhou; Hengwen Tang; Jing Liu; Jianru Tang; Xiaohua Zhu; Youyu Zhang; Meiling Liu (Analytica Chimica Acta, 2026)

Organophosphate flame retardants and immunotoxicity: An integrated bibliometric and systematic review of epidemiological and mechanistic evidence - Chengyue Ma; Yuhao Zhong; Xiaowen Huang; Minghui Li; Jinsong Zhao; Chunji Wang; Fang Zhang; Yue Jia; Yuxin Jiang; Yingli Li; Meiling Shi; Shuqi Chen; et al. (Journal of Environmental Sciences, 2026)

Genome-wide analysis of the papaya bZIP gene family identifies CpbZIP52 as a key regulator of fruit postharvest ripening - Meiling Ding; Shanni Cao; Meng Zeng; Min Zhang; Hongya Tang; Xiaochun Chen; Xianqi Fu; Sicheng Bai; Min Yang; Kaidong Liu (Plant Science, 2026)

SEMA4A promotes acute myeloid leukemia progression through inhibiting apoptosis - Xinyu Li; Binyu Yao; Meiling Sun; Wangshi Li; Xingzhi Lv; Keyang Luo; Yue Wu; Ruolin Xiu; Yuzhu Ma; Fukai Liu; Yanhong Zhao; Shengjin Fan; et al. (Genes & Genomics, 2026)

Shifting patterns in tropical lake phytoplankton communities coinciding with anthropogenic nutrient and pollutant trends - Dongna Yan; Yongming Han; Patrick Rioual; Jianghu Lan; Sifan Zan; Yalan Tang; Huijia Zhang; Meiling Guo; Eric Capo (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Microbial-driven iron transformation and carbon stabilisation in flooded soils: roles of biochar and rock weathering - Qiao Xu; Gefeng Zhang; Feifan Zhang; Tharanga Bandara; Hongyan Guo; Meiling Xu; Caixian Tang (Plant and Soil, 2026)

Reciprocal rate-modulated evolution of slow-moving reservoir landslide: learning from hydrological-adapted block model - Shu Zhang; Qiang Li; Huiming Tang; Zongxing Zou; Jianfan Zhao; Jiefei Zhang; Meiling Wu (Landslides, 2026)

2,2',4,4'-tetrabromodiphenyl ether (BDE-47) induces early hearing loss in guinea pigs via activating AhR to trigger mitochondrial and endoplasmic reticulum stress-regulated autophagy - Jie Tang; Li Zhang; Yujia Yang; Chunji Wang; Fang Zhang; Muxin Yu; Nenghua Zhang; Guangtao Xu; Bo Hu; Meiling Shi; Long Xu (Archives of Toxicology, 2025)

Wheat yield prediction using an enhanced WOFOST with soil stratified hydrothermal module driven by GLASS and ERA5-land products over Yellow River Basin - Jing Zhang; Guijun Yang; Meiling Gao; Lijie Zhang; Weinan Chen; Miao Liu; Youming Zhang; Aohua Tang; Zhenhong Li (Computers and Electronics in Agriculture, 2025)

Towards robust partial nitrification in low-ammonia wastewater: Electrospinning nanofiber composite-enhanced hydrogel beads immobilized comammox Nitrospira - Peng Tang; Liangang Hou; Meiling Yin; Feng Huang; Zhengwei Pan; Tianhao Shi; Jun Li; Yuhan Zhu; Xin Zhang; Peng Gao (Bioresource Technology, 2025)

Comparison of efficacy and safety of dual orexin receptor antagonists lemborexant and daridorexant for the treatment of insomnia: a systematic review and meta-analysis - Ming Tang; Ziyi Shen; Peilu Yu; Meiling Yu; Xiaoqiong Tong; Guohui Jiang (Psychopharmacology, 2025)

Arthrospira platensis polysaccharide alleviates inflammation induced by PRV in RAW264.7 cells and mice via the regulation of LncRNA Dhx35/mmu-miR-185-3p/IL-17RA - Shouli Yi; Xiaodong Xie; Xiaoli Yu; Min Tang; Duong Thi Toan; Meiling Yu; Mixia Cao; Tingjun Hu (Algal Research, 2025)

Microbial mechanism and CO2 emission from coastal saline soil: The role of corn stover and nutrient additions - Qiao Xu; Ling Zhang; Yingdong Zhao; Caixian Tang; Yinjuan Li; Meiling Xu; Xiaozhi Wang (Environmental Research, 2025)

Detection of whey protein concentrate adulteration using laser-induced breakdown spectroscopy combined with machine learning - Meiling Zhu; Weiran Song; Xuan Tang; Xiangzeng Kong (Food Additives & Contaminants: Part A, 2025)

Unraveling the trisubstrate-triproduct reaction mechanisms of wine grape VvCYP76F14 to improve wine bouquet - Zhizhong Song; Meiling Tang; Huilin Xiao; Houhua Xu; Matthew Shi; Adeeba Dark; Zhenqiang Xie; Bin Peng (Food Chemistry, 2025)

Anemarrhenae rhizoma combined with Trichosanthis radix ameliorated type 2 diabetes in rats via the PI3K-Akt signalling pathway based on network pharmacology analysis - Yan Lin; Jinde Zheng; Xinyi Zhao; Bei Zheng; Ying Li; Wenjuan Yang; Bing Han; Hanxiao Tang; Meiling Zhang (Natural Product Research, 2025)

Estimation of winter wheat yield by assimilating MODIS LAI and VIC optimized soil moisture into the WOFOST model - Jing Zhang; Guijun Yang; Junhua Kang; Dongli Wu; Zhenhong Li; Weinan Chen; Meiling Gao; Yue Yang; Aohua Tang; Yang Meng; Zhihui Wang (European Journal of Agronomy, 2025)

Saikosaponins alleviate depression-like behaviors of chronic unpredictable mild stress exposed mice through ERK signaling pathway - Min Chen; Min Li; Liwei Ma; Huiling Hou; Meiling Tang; Qiang Li (Experimental Brain Research, 2025)

Expanding the electrochemical stable window of water through propylene carbonate addition for aqueous-based energy storage devices - Meiling Tang; Yu Meng; Yibing Yang; Shuilin Wu (Chemical Engineering Journal, 2025)

Evaluation of the gully erosion susceptibility by using UAV and hybrid models based on machine learning - Qian Wang; Bohui Tang; Kailin Wang; Jiannan Shi; Meiling Li (Soil and Tillage Research, 2024)

Bacteria contribute more than fungi to SOC decomposition in a paddy field under long-term free-air CO2 enrichment - Meiling Xu; Feifan Zhang; Ling Zhang; Hongze Zhang; Caixian Tang; Xiaozhi Wang; Jing Ma; Qiao Xu (European Journal of Soil Biology, 2024)

Different activation of STAT1 and STAT2 phosphorylation by IFNc, IFNd, and IFNh in tilapia - Qingqing Wen; Shaoshuai Tang; Jingyi Mo; Meiling Zhang; Meng Long; Yishan Lu; Zhen Gan (Fish & Shellfish Immunology, 2024)

A new method of alkalinity remediation for Cd-contaminated groundwater by PAAS-modified MgCO3/Mg(OH)2 colloid - Bowen Li; Meiling Tang; Peng Wang; Shibin Liu; Meng Yao; Jun Dong (Chemosphere, 2024)

Subalpine peatland development since the Last Glacial Maximum in subtropical China: Predominantly controlled by monsoonal climate and local topography - Cong Chen; Kangyou Huang; Dehao Xie; Meiling Man; Yongjie Tang; Yuanfu Yue; Xiao Zhang; Zhuo Zheng; Rachid Cheddadi (CATENA, 2024)

The role of cyclin-dependent kinase inhibitor 3 in the proliferation and migration of renal cell carcinoma - Chenbo Ni; Zhisheng Guo; Hengtao Bu; Xusong Zhao; Meiling Bao; Lei Ding; Chao Liang; Qingsheng Tang; Jie Li (Chemico-Biological Interactions, 2024)

Calcium polypeptide mitigates Cd toxicity in rice via reducing oxidative stress and regulating pectin modification - Hongbing Chen; Xiaojun Tang; Tiejun Wang; Weifang Liao; Zhixian Wu; Meiling Wu; Zhihao Song; Yadong Li; Pan Luo (Plant Cell Reports, 2024)

Response of sediment microbial communities to the flow effect of the triangular artificial reef: A simulation-based experimental study - Meiling Zhu; Yanli Tang (Marine Environmental Research, 2024)

Correction to: Characteristics of splenic PD-1+ γδT cells in Plasmodium yoelii nigeriensis infection - Dianhui Chen; Feng Mo; Meiling Liu; Lin Liu; Junmin Xing; Wei Xiao; Yumei Gong; Shanni Tang; Zhengrong Tan; Guikuan Liang; Hongyan Xie; Jun Huang; et al. (Immunologic Research, 2024)

Characteristics of splenic PD-1+ γδT cells in Plasmodium yoelii nigeriensis infection - Dianhui Chen; Feng Mo; Meiling Liu; Lin Liu; Junmin Xing; Wei Xiao; Yumei Gong; Shanni Tang; Zhengrong Tan; Guikuan Liang; Hongyan Xie; Jun Huang; et al. (Immunologic Research, 2024)
Although the functions of programmed death-1 (PD-1) on αβ T cells have been extensively reported, a role for PD-1 in regulating γδT cell function is only beginning to emerge. Here, we investigated the phenotypic and functional characteristics of PD-1-expressing γδT cells, and the molecular mechanism was also explored in the Plasmodium yoelii nigeriensis ( P. yoelii NSM)-infected mice . Flow cytometry and single-cell RNA sequencing (scRNA-seq) were performed. An inverse agonist of RORα, SR3335, was used to investigate the role of RORα in regulating PD-1 + γδT cells. The results indicated that γδT cells continuously upregulated PD-1 expression during the infection period. Higher levels of CD94, IL-10, CX3CR1, and CD107a; and lower levels of CD25, CD69, and CD127 were found in PD-1 + γδT cells from infected mice than in PD-1 − γδT cells. Furthermore, GO enrichment analysis revealed that the marker genes in PD-1 + γδT cells were involved in autophagy and processes utilizing autophagic mechanisms. ScRNA-seq results showed that RORα was increased significantly in PD-1 + γδT cells. GSEA identified that RORα was mainly involved in the regulation of I-kappaB kinase/NF-κB signaling and the positive regulation of cytokine production. Consistent with this, PD-1-expressing γδT cells upregulated RORα following Plasmodium yoelii infection. Additionally, in vitro studies revealed that higher levels of p-p65 were found in PD-1 + γδT cells after treatment with a RORα selective synthetic inhibitor. Collectively, these data suggest that RORα-mediated attenuation of NF-κB signaling may be fundamental for PD-1-expressing γδT cells to modulate host immune responses in the spleen of Plasmodium yoelii nigeriensis –infected C57BL/6 mice, and it requires further investigation.

Validation of endogenous U6 promoters for expanding the CRISPR toolbox in Nicotiana tabacum - Pan Luo; Siyuan Li; Lulu Li; Yanyan Li; Ying Qiao; Xianzhi Wu; Meiling Wu; Zhihao Song; Yong Yang; Ji Feng; Xingchun Tang (In Vitro Cellular & Developmental Biology - Plant, 2024)

All-in-one treatment: Capture and immobilization of 137Cs by ultra-stable inorganic solid acid materials HMMoO6·nH2O (M = Ta, Nb) - Zhihua Chen; Shaoqing Jia; Haiyan Sun; Junhao Tang; Yanling Guo; Yuexin Yao; Tianyu Pan; Meiling Feng; Xiaoying Huang (Water Research, 2024)

Pt,P-codoped carbon nitride nanoenzymes for fluorescence and colorimetric dual-mode detection of cholesterol - Meiling Chen; Yang Yang; Qinhua Chen; Lina Tang; Junlin Liu; Yujie Sun; Qiming Liu; Yulin Zhang; Guo-jun Zhang; Shaowei Chen (Analytica Chimica Acta, 2024)

Increased black carbon (soot) accumulation during the Anthropocene in a less-developed region of Xinjiang, northwestern China - Dewen Lei; Yongming Han; Changlin Zhan; Chong Wei; Yalan Tang; Meiling Guo; Jianing Zhang; Jingyu Li (Anthropocene, 2024)

A prototype galectin-1 (also known as galecin-2) from large yellow croaker (Larimichthys crocea): Molecular and function study - Xin Tang; Zhiqun Xiao; Meiling Chen; Jian Jin; Chunmei Yan; Xingcheng Zhu; Zhiyong Wang; Dongling Zhang (Fish & Shellfish Immunology, 2024)

Isolation, heterologous expression, and functional determination of an iron regulated transporter (IRT) gene involved in Fe2+ transport and tolerance to Fe2+ deficiency in Vitis vinifera - Zhizhong Song; Xue Wang; Mengyuan Li; Youzheng Ning; Shengpeng Shi; Guangrong Yang; Hongxia Zhang; Meiling Tang; Bin Peng (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)
In plants, iron (Fe) regulated transporters (IRT) play important roles in uptake and transport of Fe that contributes to plant growth and development. However, biological functions of IRT transporters in fruit trees are still unknown. This study isolated 10 VvIRT genes from ‘Marselan’ grape, with varying expression levels across different tissues/organs, particularly enhanced under Fe depletion, especially in roots. Notably, VvIRT7 is the most abundantly expressed IRT gene in grape, beneficially restoring the Fe 2+ uptake defect of yeast mutant DEY1453. Furthermore, VvIRT7 showed dominant expression in the roots of irt1 /35S:: IRT7 complementation lines. Overexpressing of VvIRT7 rescued the retarded growth of irt1 knockout mutant, by increasing the fresh weight, dry weight, total root length, total root surface, lateral root numbers, total leaf chlorophyll, ACO activity, NiR activity, SDH activity, and tissue Fe concentration. This study provides insights for understanding molecular mechanisms of Fe uptake and transport in grape.

Bilobetin attenuates Staphylococcus aureus virulence by targeting Von Willebrand factor-binding protein and staphylocoagulase - Chongling Zhang; Wenyuan Zhang; Shuyue Zhu; Chunjie Hu; Sihua Che; Meiling Wang; Mengli Jin; Nan Bian; Wu Song; Shuang Jiang; Yijing Jiang; Juan Hou; et al. (World Journal of Microbiology and Biotechnology, 2023)

Savanna/rainforest dynamics and hydroclimate changes in northern boundary of tropical Asia over the past 150 kyrs - Cong Chen; Kangyou Huang; Zhuo Zheng; Yongqiang Zong; Peter Kershaw; Shixiong Yang; Liping Tian; Meiling Man; Sheng-Hua Li; Chris Brodie; Ning Wang; Xiao Zhang; et al. (Global and Planetary Change, 2023)

Insight into the molecular mechanism of phosphine toxicity provided by functional analysis of cytochrome b5 fatty acid desaturase and dihydrolipoamide dehydrogenase in the red flour beetle, Tribolium castaneum - Xu Shen; Meiling Che; Honglei Xu; Xinbo Zhuang; Erhu Chen; Peian Tang; Kangxu Wang (Pesticide Biochemistry and Physiology, 2023)

Numerical study of regular wave-induced oscillatory soil response during the caisson installation - Lunliang Duan; Chenxi Qin; Jianting Zhou; Guangwu Tang; Duoyin Wang; Meiling Fan (Ocean Engineering, 2023)

Ag2S QDs integration with MnO2 nanosheets for the sensitive detection of Cr (VI) via the redox reaction induced photoelectrochemical variation - Lili Zhao; Haoyu Chen; Ying Tang; Peipei Li; Xiaohua Zhu; Jingyi Liu; Meiling Liu; Youyu Zhang; Shouzhuo Yao (Analytica Chimica Acta, 2023)

Research progress on antidiabetic activity of apigenin derivatives - Jingyi Jiang; Ting Tang; Yaling Peng; Meiling Liu; Qianwen Liu; Pengbing Mi; Zehua Yang; Hongfei Chen; Xing Zheng (Medicinal Chemistry Research, 2022)

Liver kinase B1 (LKB1) reduced inflammation and oxidative stress by regulating the AMPK/NLRP3 signaling pathway in LPS-induced lung injury - Yifeng Yue; Liwu Zong; Yongmin Chen; Nianhai Feng; Junxia Tang; Hongyu Xu; Meiling Zhao (Molecular & Cellular Toxicology, 2021)